Rancang Bangun Alat Penyiram Tanaman Anggrek Otomatis Berbasis Arduino Menggunakan Sensor Waktu dan Sensor Gerak - Nurul Maulana; Munaf Ismail (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Limited time and human negligence in regular orchid watering can reduce plant growth quality and increase the risk of plant damage. This study aims to design an Arduino-based automatic orchid watering device integrated with time and motion sensors to improve watering efficiency and maintain plant care consistency. The research employed a research and development (R&D) approach through prototype design, hardware integration, software implementation, and functional testing. The developed system consists of an Arduino Uno, DHT11 temperature sensor, Passive Infrared (PIR) sensor, RTC DS3231, relay, LCD I2C, buzzer, and water pump. The testing results showed that the prototype successfully detected environmental conditions, displayed temperature information in real-time, and activated the watering mechanism automatically at 07:00 WIB and 19:00 WIB or when the temperature exceeded 32°C. The integration of motion detection also improved operational safety by delaying watering when human activity was detected around the plant area. This innovation provides a practical solution for supporting efficient orchid maintenance in small-scale cultivation environments.